Thymic plasmacytoma presenting as polyneuropathy and revealing multiple myeloma: a case report - Syrine Laroussi; Khadija Sonda Moalla; Faten Kallel; Saadia Makni; Nozha Kallel; Nouha Farhat; Mariem Damak; Moez Elloumi; Tahya Sellami; Khaireddine Ben Mahfoudh; Chokri Mhiri (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Multiple myeloma (MM) is the most frequent malignant plasma cell disorder with proliferation of neoplastic plasma cells in the bone marrow or other tissue, most commonly in the upper aerodigestive tract. The invasion of the thymus is exceptional. Neurological complications are usual, but represent exceptionally the revealing symptom. Case presentation We report a case of polyneuropathy revealing a thymic plasmacytoma as a mediastinal invasion of MM in a 48-year-old woman. She was admitted after developing progressive ascending distal paresthesias and weakness in lower limbs. Examination showed symmetrical distal sensorimotor impairment with axillary and inguinal adenopathies. Electroneuromyography revealed a sensorimotor length-dependent neuropathy. Serum protein electrophoresis showed monoclonal protein peak in β-γ globulin region. Immunoelectrophoresis showed IgA lambda monoclonal gammapathy. Myelogram and bone marrow biopsy revealed plasmocytosis of 5%. Chest computed tomography showed a histologically confirmed thymic plasmacytoma associated with a lytic lesion of the 5th rib leading to the diagnosis of MM. Conclusions The association between a thymic plasmacytoma and peripheral neuropathy is rare and a workup for MM is necessary to guide therapeutic management.